The Effect Of Motivation And Career Development On Employee Performance Of Pt. Wisma Seratus Sejahtera - Amrulloh, Muhammad Almas Abror; Gani, Nur Asni (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to: (1) determine and analyze the influence of motivation on employee performance at PT. Wisma Seratus Sejahtera. (2) Determine and analyze the influence of career development on employee performance at PT. Wisma Seratus Sejahtera. (3) Determine and analyze the influence of motivation and career development on employee performance at PT. Wisma Seratus Sejahtera. This study uses a quantitative method with an associative research type, which tests the relationship between independent variables (motivation and career development) and dependent variables (employee performance). Based on this study, it is concluded that motivation has a positive influence on employee performance at PT. Wisma Seratus Sejahtera, but the influence is not significant. This means that although motivation can drive performance, other factors may be more dominant in determining employee work results. On the other hand, career development has been shown to have a positive and significant influence on employee performance. The better the company provides career development opportunities, the higher the performance achieved by employees. In addition, motivation and career development together have a positive and significant influence on employee performance. These two factors support each other in encouraging employees to achieve better performance. Overall, career development has a greater influence in improving employee performance compared to motivation alone.